PENGARUH FINANCIAL TECHNOLOGY TERHADAP INKLUSI KEUANGAN DENGAN LITERASI KEUANGAN SEBAGAI VARIABEL INTERVENING PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Putri, Resy Selviana Retno; Wiryaningtyas, Dwi Perwitasari; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The development of technology and information brings very rapid changes in human life. One of them is the innovation in non-cash payments along with the increasing development of technology. The purpose of this study was to analyze and examine the effect of financial technology on financial inclusion with financial literacy as an intervening variable for students of the Faculty of Economics and Business, Abdurachman Saleh University, Situbondo. The sampling technique was determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that financial technology has a significant effect on financial literacy, financial technology has a significant effect on financial inclusion. Financial literacy has a significant effect on financial inclusion. The results of the indirect effect hypothesis test show that the financial technology variable has a significant positive.